Comparison of Efficacy of Family Cognitive–Behavioral Therapy (FCBT) and Mother - Child Attachment Intervention in Separation Anxiety Disorder in Children between 7-12 years old - Gerami, Sahel; Ghodsi, Parvaneh; MohammadKhani, Parvaneh; Taghiloo, Sadegh (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The purpose of this study was to compare and evaluate the effectiveness of Family Cognitive–Behavioral Therapy (FCBT) and Mother - Child Attachment Intervention in Separation Anxiety Disorder in Children Between 7-12 years old. Methods: The method of this semi-experimental study was a pre-test-post-test type with a control group and a three-month follow-up. For this purpose, 36 children with separation anxiety disorder were selected by purposive sampling and were divided into three groups of 12 people. The first group of cognitive behavioral therapy based on the family of Kendall and Hetke (2006) and the adapted Goala of Barrett et al. (1996), the second course of mother-child attachment intervention Pernell (2004) and King Newnham (2008) in eight sessions of 60 minutes. and the control group did not receive any intervention. The measurement tools of this research included the semi-structured diagnostic interview of mood disorders and schizophrenia for children and adolescents by Archvalta, Folioux, and Martinez (2006), the separation anxiety scale (parent form) by Han, Hajinlian, and Isen (2003). The data were analyzed using mixed variance analysis with repeated measurement and Ben Feroni's post hoc test. Results: The findings show that family-oriented cognitive-behavioral therapy has been more effective in reducing children's separation anxiety compared (F=19.68, P=0.001) to mother-child attachment intervention (P